(untitled) (Research, Society and Development, 2022)
Burnout Syndrome (BS) is characterized as an occupational disease. Among the factors linked to the development of BS, issues related to working conditions have a significant weight. Thus, the study aimed to study aims to verify if the teaching network in which teachers teach, Municipal, State and Federal, has an influence on the development of BS and its related factors. It is characterized as a descriptive diagnostic study, with teachers from Municipal, State and Federal public schools in Uruguaiana/RS. 91 teachers were part of the study, 40 from the state network, 31 from Municipal network and 20 from the Federal education network. To evaluate the BS, the JBEILI Inventory inspired by the Maslach Burnout Inventory for BS was used, associated with a questionnaire developed by the authors to survey other variables. The results of the study did not find any statistically significant value for the average BS indexes among the education networks, however, a correlation was found between the BS score and the workload and income in the Municipal network. It was found that the presence of BS was significantly associated with income, with 43.2% of teachers with the indication of BS, being in the lowest financial class. The State network showed a significant association with teaching time, as well as the Municipal network presented BS associated with the younger age group. The study obtained valuable information, pointing out the need for interventions aimed at the mental health of teachers, in addition to more studies involving this population.